ARE THE INTERESTS OF BUSINESS ACTORS AND CONSUMERS BALANCED IN THE INDONESIAN COMPETITION LAW? - Moch Zairul Alam; Kukuh Tejomurti (Dialogia Iuridica, 2022)
This paper aims to provide a critical analysis to the relations between economic efficiency and justice as the objectives of business competition law in Indonesia within the framework of legal philosophy. Philosophical aspects explores view on equal opportunities for every citizen in their business behavior, relation between the principles of justice and efficiency considering that in the Law 5 of 1999 there is no any word “justice” mentioned. Several related schools of legal philosophy will use to analyse the problems, such as, Utilitarianism in dissecting the phrase "public interest and welfare", John Stuart Mill's theory of lliberty in examining "equal opportunities for citizens", The article uses the legal research by emphasising the critical analysis on economic efficiency and justice principles in Indonesian competition law and compare FTC. Article 3 of Law Number 5 of 1999 aims to improve economic efficiency as one of the efforts to improve people's welfare. From a philosophical point of view, people's welfare law is closely related to the "greatest benefit for the greatest people" (Jeremy Bentham). However, if we look at the interests between business actors and consumers, thiscondition can still be seen that the interest in efficiency still prioritizes the interests of business actors. Fulfilment of consumer justice is only placed as an "object" rather than a subject whose rights must be protected due to violations of business competition.